2013
DOI: 10.1136/thoraxjnl-2012-203035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cytisine in helping smokers quit: systematic review and meta-analysis

Abstract: Background A recent rigorous study has shown that cytisine, a low-cost drug, is effective for smoking cessation. A number of earlier studies exist, mostly from former communist countries where cytisine has been used since the 1960s. The key question now is whether there is sufficient evidence to warrant licensing cytisine or whether more work is needed. A systematic review was undertaken to assess the efficacy of cytisine in smoking cessation. Methods The Cochrane Library, CINAHL, Embase, Medline and PsycINFO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 20 publications
4
76
0
6
Order By: Relevance
“…Moreover, we also have the very low-cost drug, cytisine, as an option [18]. This raises a serious question as to whether substantial further investment in nicotine vaccines will be worthwhile from either commercial or public health perspectives.…”
mentioning
confidence: 99%
“…Moreover, we also have the very low-cost drug, cytisine, as an option [18]. This raises a serious question as to whether substantial further investment in nicotine vaccines will be worthwhile from either commercial or public health perspectives.…”
mentioning
confidence: 99%
“…Despite this, only two trials of good quality with a minimum of 6 months' follow-up that have evaluated the clinical efficacy of cytisine compared with placebo met the inclusion criteria for both the Cahill review 15 and the current review. The Hajek review 26 of cytisine identified more trials; however, these did not fit the inclusion criteria for the Cahill review 15 or this current review. The most common reason for this was that the length of follow-up was too short.…”
Section: Clinical Effectiveness Findingsmentioning
confidence: 99%
“…A recent review of the efficacy and safety of cytisine found it to be an effective treatment for smoking cessation. 26 The review highlights the low cost of cytisine and suggests that licensing of this drug may therefore be warranted because of its potential public health benefit. No head-to-head trials between varenicline and cytisine were identified in either review and, to date, no indirect comparisons of the two drugs have been conducted in the absence of such trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then a number of studies have demonstrated its efficacy. A pragmatic, open-label, non-inferiority trial with 1310 adult daily smokers, noted that when combined with behavioural support, cytisine promotes continuous abstinence at 6 months to a greater extent than NRT; while a Cochrane systematic review reported that cytisine was four times more effective than placebo [77,78].…”
Section: Relative Efficacymentioning
confidence: 99%